Protected Area Rangers as Cultural Brokers? Implications for Wildlife Crime Prevention in Viet Nam - Rizzolo, Jessica B.; Gore, Meredith L.; Long, Barney; Trung, Cao T.; Kempinski, Josh; Rawson, Benjamin; Huyẽn, Hoàng T.; Viollaz, Julie (Frontiers in Conservation Science, 2021)
The scope, scale, and socio-environmental impacts of wildlife crime pose diverse risks to people, animals, and environments. With direct knowledge of the persistence and dynamics of wildlife crime, protected area rangers can be both an essential source of information on, and front-line authority for, preventing wildlife crime. Beyond patrol and crime scene data collected by rangers, solutions to wildlife crime could be better built off the knowledge and situational awareness of rangers, in particular rangers’ relationships with local communities and their unique ability to engage them. Rangers are often embedded in the communities surrounding the conserved areas which they are charged with protecting, which presents both challenges and opportunities for their work on wildlife crime prevention. Cultural brokerage refers to the process by which intermediaries, like rangers, facilitate interactions between other relevant stakeholders that are separate yet proximate to one another, or that lack access to, or trust in, one another. Cultural brokers can function as gatekeepers, representatives, liaisons, coordinators, or iterant brokers; these forms vary by how information flows and how closely aligned the broker is to particular stakeholders. The objectives of this paper are to use the example of protected area rangers in Viet Nam to a) characterize rangers’ cultural brokerage of resources, information, and relationships and b) discuss ranger-identified obstacles to the prevention of wildlife crime as an example of brokered knowledge. Using in-depth face-to-face interviews with rangers and other protected area staff (N = 31, 71% rangers) in Pu Mat National Park, 2018, we found that rangers regularly shift between forms of cultural brokerage. We offer a typology of the diverse forms of cultural brokerage that characterize rangers’ relationships with communities and other stakeholders. We then discuss ranger-identified obstacles to wildlife protection as an example of brokered knowledge. These results have implications for designing interventions to address wildlife crime that both improve community-ranger interactions and increase the efficiency of wildlife crime prevention.